Pengaruh Karakteristik Individu Terhadap Minat Kunjungan Ulang Pemeriksaan Antenatal Care (ANC) Di Rumah Sakit Umum Ridos Medan Tahun 2024 - Polma Ria Metawati Panjaitan; Mediana Br. Sembiring (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Antenatal Care (ANC) examinations are an important strategy in reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), which are currently still high. Ridos Medan General Hospital is one of the hospitals that provides Antenatal Care (ANC) examinations with a low percentage of pregnant women who make repeat visits for Antenatal Care (ANC) examinations, namely 889 pregnant women who carry out Antenatal Care (ANC) examinations while those who do There will only be 498 pregnant women repeat visits for Antenatal Care (ANC) examinations in 2022. This type of research is a survey with an explanatory research type, which aims to explain the influence of individual characteristics (age, education, occupation, parity, health condition, pregnancy interval, income). , distance, attitude, knowledge, husband's support, and satisfaction with health workers) on interest in repeat visits for Antenatal Care (ANC) examinations at Ridos Medan General Hospital in 2023. The research was conducted at Ridos Medan General Hospital. The population in this study were pregnant women. The sampling technique was Accidental Sampling as many as 89 people. The data analysis used is multiple linear regression. The results of the study show that the variables that influence interest in repeat visits for Antenatal Care (ANC) examinations are education, knowledge, attitudes and satisfaction with health workers. The contribution of these four variables to interest in repeat visits for Antenatal Care (ANC) examinations was 57%. Of the four variables, the one with the strongest influence on interest in repeat visits for Antenatal Care (ANC) examinations is knowledge (B=0.475). Respondents' interest in repeat visits for Antenatal Care (ANC) examinations was generally in the low category, namely 40.4%, medium at 32.6%, and high interest in repeat visits for Antenatal Care (ANC) examinations at 27.0%. In an effort to increase interest in repeat visits for Antenatal Care (ANC) examinations, efforts must be made, namely advocacy and socialization about Antenatal Care (ANC) examinations, carrying out Antenatal Care (ANC) examinations according to standards, training related health workers and it is hoped that health workers will improve the quality of service by being friendlier, more alert, attentive and clear in conveying information.